India-Japan Ties: Contemporary Aspects - Yadav, Baljeet; Kumar, Mukesh (Journal of Innovation in Education and Social Research, 2025)
The India-Japan relationship has evolved into one of Asia's most significant strategic partnerships, transcending traditional bilateral cooperation to encompass multifaceted dimensions of economic security, technological innovation, and geopolitical collaboration. This research examines the contemporary aspects of Indo-Japanese relations through comprehensive analysis of bilateral trade dynamics, investment patterns, defense cooperation frameworks, and emerging technological partnerships. The study employs both quantitative and qualitative methodologies to assess the current state and future trajectory of this partnership. Key findings indicate that bilateral trade has reached USD 25.15 billion in FY 2024-25, with Japan's commitment to invest USD 68 billion by 2027 under the Vision 2025 framework representing a paradigm shift in economic engagement. The research reveals that contemporary India-Japan ties are characterized by strategic convergence in Indo-Pacific security architecture, deepening economic integration through the Comprehensive Economic Partnership Agreement (CEPA), and collaborative approaches to emerging challenges including supply chain resilience and technological sovereignty. The analysis demonstrates that this partnership serves as a cornerstone for regional stability and economic prosperity, with implications extending beyond bilateral benefits to encompass broader regional and global governance structures.